IncF plasmid diversity in multi-drug resistant Escherichia coli strains from animals in China - Yang, Qiu E.; Sun, Jian; Li, Liang; Deng, Hui; Liu, Bao T.; Fang, Liang X.; Liao, Xiao p.; Liu, Ya H. (Frontiers in Microbiology, 2015)
The purpose of this study was to characterize a collection of 103 multidrug resistance IncF plasmids recovered from Escherichia coli of food producing and companion animals between 2003 and 2012. A total of 103 incF plasmids were characterized using an established PCR-based IncF replicon sequence typing (RST) system to identify FII, FIA and FIB (FAB) groups. Plasmids were also analyzed using-restriction fragment length polymorphism (RFLP). Antibiotic Resistance determinants blaCTX-M, plasmid-mediated quinolone resistance (PMQR) genes and rmtB and plasmid addiction systems (PAS) were identified by PCR screening. A total of 20 different RSTs from 103 IncF plasmids were identified. The groups F2 and F33 with the RST formulae A-: B- were the most frequently encountered types (63.1%). The antibiotic resistance genes blaCTX-M, rmtB and oqxB were carried by 82, 37 and 34 IncF plasmids, respectively. Most of these plasmids carried more than one resistance gene (59.2%, 61/103). The IncF plasmids also had a high frequency of addiction systems (mean 2.54) and two antisense RNA-regulated systems (hok–sok and srnBC) and a protein antitoxin-regulated system (pemKI) were the most prevalent. Not surprisingly, RFLP profiles among the IncF plasmids were diverse even though some shared identical IncF-RSTs. This is the first extensive study of IncF plasmid-positive E. coli isolates from animals in China. Our results demonstrate that IncF is the most prevalent plasmid family in E.coli plasmids and they commonly carry multiple resistance determinants that render them resistant to different antibiotic classes simultaneously. IncF plasmids also harbor addiction systems, promoting their stability and maintenance in the bacterial host, under changing environmental conditions.